(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to carry out a literature review to describe the clinical characteristics of Monkeypox, explain its means of transmission, and favor its prevention. Methodology: Searches using descriptors in PUBMED Central, BVS/BIREME, Web of Science, Scielo, The Cochrane Library, Google Scholar, and books on the subject, classified as gray literature. Results: During the review process on the therapeutic options available for the treatment and prevention of the disease, it can be concluded that the population’s access to efficient health has become essential, so that there is effective control of this disease, through vaccination, prevention programs, and information to the population about the means of transmission.